Efficient fabrication of polymer nanoparticles via sonogashira cross‐linking of linear polymers in dilute solution. Issue 1 (20th October 2015) - Prasher, Alka; Loynd, Conor M.; Tuten, Bryan T.; Frank, Peter G.; Chao, Danming; Berda, Erik B.
ABSTRACT: The synthesis of single‐chain nanoparticles by palladium‐catalyzed Sonogashira coupling between a terminal alkyne and a di‐halo aryl cross‐linker is reported. Statistical copolymers with trimethylsilyl protected alkyne groups pendent to the linear methacrylate back bones were synthesized using reversible addition‐fragmentation chain transfer polymerization post polymerization de‐protection providing terminal alkyne functionalized linear polymer chains. These linear polymer chains were intramolecularly cross‐linked via bifunctional cross‐linkers. The resulting well‐defined covalently bonded nanoparticles were characterized via triple‐detection size exclusion chromatography where MALS detector provided molecular weight information and viscometric detection characterizes particle size and conformations. The particle size could be readily tuned through polymer molecular weight and by degree of cross‐linking. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 209–217 Abstract : Palladium catalyzed Sonogashira coupling is presented as an efficient method for nanoparticle fabrication in dilute solutions. Introduction of a bifunctional cross‐linker induces cross‐linking in linear polymers. The cross‐linking phenomenon can be modulated by changing the concentration of the reaction mixture. 1 H NMR spectroscopy and triple detection size‐exclusion chromatography confirm the cross‐linking phenomenon, and TEM images provide visual evidence for particle formation.